ORIENTATION OF PANCASILA IDEOLOGY ACCULTURATION (A Preliminary Study of the Relationship between Political-Regime Character and Acculturation Orientation of Pancasila Ideology) - Razuni, Ganjar (CosmoGov: Jurnal Ilmu Pemerintahan, 2023)
This paper examines the orientation of the acculturation of the Pancasila ideology in each period of the era of the Indonesian political system, namely, the age of Western-style Liberal / Parliamentary Democracy November 3 1945-July 5, 1959, the first volume of liberal democracy in Indonesia; the Soekarno Guided Democracy era July 5 1959-March 12 1967, the Soeharto New Order era March 12 1967-May 21 1998. This era was followed by the post-1998 Reformation era, which consisted of: the era of Liberalization or Ultra-Liberal Democracy Volume Two and; the period of the rediscovery of Pancasila ideology in Indonesian social, national and state life 2018-present (Rediscovery of Pancasila Ideology) amid the era of Ultra-Liberal Democracy / Liberal Democracy Volume Two. This study aims to construct the orientation of Pancasila ideology acculturation and its implementation in each period of the political system from an ideological perspective and regime character as a background to formulate the right Pancasila ideology acculturation according to the needs of the times without being uprooted from the philosophic roots, ideological roots, historical roots and intellectual roots of Pancasila ideology while innovating Pancasila ideology acculturation to fight the weakening of the nation from within itself.gb777